2022
DOI: 10.1186/s12909-022-03518-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of electrocardiogram interpretation competency among healthcare professionals and students of Ardabil University of Medical Sciences: a multidisciplinary study

Abstract: Background Electrocardiogram (ECG) interpretation is a core clinical skill that helps to rapid diagnosis of potentially life-threatening diseases. Misinterpretation of the electrocardiogram can lead to inappropriate clinical decisions with adverse outcomes. The main aim of this survey was to assess the competency of electrocardiogram interpretation and related factors among healthcare professionals and students of Ardabil University of Medical Sciences. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…These findings almost mirrored the study of Vishnevsky et al [ 10 ], where the overall competency mean score was 3.23 (SD 1.81) out of 8 points, suggesting a low level of competency. This corroborates the study of Amini et al [ 12 ], with a mean competency score of 5.13 (SD 2.25) out of 10 points. Surprisingly, a study conducted by Oluga [ 15 ] showed the least prevalence of low ECG skills competency, as only 2.8% of the medical students were able to interpret correctly at least 50% or more of the 22 ECG cases, adding that the medical students in University Nairobi have suboptimal competency levels in ECG interpretation skills.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings almost mirrored the study of Vishnevsky et al [ 10 ], where the overall competency mean score was 3.23 (SD 1.81) out of 8 points, suggesting a low level of competency. This corroborates the study of Amini et al [ 12 ], with a mean competency score of 5.13 (SD 2.25) out of 10 points. Surprisingly, a study conducted by Oluga [ 15 ] showed the least prevalence of low ECG skills competency, as only 2.8% of the medical students were able to interpret correctly at least 50% or more of the 22 ECG cases, adding that the medical students in University Nairobi have suboptimal competency levels in ECG interpretation skills.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, regarding the details of competency in interpreting each ECG strip, many of our subjects were able to correctly interpret ECG strips about anterior MI (69.3%), ventricular tachycardia (65.6%) and normal ECG (60.2%), which is similar to the results of Vishnevsky et al [ 10 ] where many of their students were able to interpret anterior MI (81%), ventricular tachycardia (54%), and normal ECG (65%). On the other hand, in Iran [ 12 ], only a minority of students were able to identify normal sinus rhythm (36.2%) and acute myocardial infarction (22.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrocardiogram (ECG) is considered an important assessment tool, and accurate clinical judgment is directly related to the correct interpretation of the ECG [ 52 ]. In a study by Amini et al in Iran, ECG interpretation skills of medical staff and students are low [ 53 ]. Research shows that a structured curriculum can improve nursing students’ ECG interpretation knowledge [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed poor performance of the medical interns in ECG interpretation, which is compatible with the results of a previous study in Iran on the ECG interpretation competency of healthcare providers and students. That study reported low ECG interpretation competency, with an average score of 5.3 ± 2.2 and a top score of 10 [ 15 ]. Similarly, Jablonover et al found the suboptimal performance of graduating medical students in ECG interpretation, with only eight (37%) of 22 key ECGs correctly identified [ 16 ].…”
Section: Discussionmentioning
confidence: 99%